Viability and characteristics of frozen thawed semen in Hanwoo - Na, G. J. (Malaysian Society of Animal Production, 2018)
Thirteen Hanwoo bulls at Daekwanryung branch of National Livestock Research Institute, Korea were examined for their semen quality. The average volume of semen, sperm counts, pH, and viability were examined for qualification as seedstock bulls.